Monopoly pricing under a Medicaid-style most-favored-customer clause and its welfare implication - Peter Klibanoff; Tapas Kundu (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2009)
To control Medicaid's increasing expenditure on reimbursement of outpatient prescription drugs, the Omnibus Budget Reconciliation Act of 1990 included a rebate program that featured a most favored customer (MFC) clause. This clause guarantees that Medicaid gets a fixed rebate on each unit of purchase by Medicaid consumers. The rebate is calculated as the difference between the minimum price and the average manufacturer price (minimum price provisioning or MPP) or a proportion of the average manufacturer price (average price provisioning or APP). We characterize the optimal pricing strategy of a third-degree price discriminating monopolist in response to the imposition of MPP or APP rules. Under MPP, the minimum price gross of rebate always increases whereas prices gross of rebate in at least some of the markets always decrease. In contrast, under APP, these prices may move in the same direction in all markets, with all increasing in some circumstances and all decreasing in others. We also examine the effects of such provisions on social welfare and provide some useful sufficient conditions for directional changes in social welfare. For example, imposing MPP increases social welfare if it results in higher aggregate demand. Beyond the Medicaid setting, minimum price policies are relevant in a number of applications, including external referencing in drug pricing, price protection in long-term trading contracts and shifts of consumers between markets. We analyze a modified version of our Medicaid MPP model suitable for such settings.
Keywords: 330; Preismanagement; Rabatt; Monopol; Arzneimittelmarkt; Gesundheitskosten; Gesetzliche Krankenversicherung; Sozialleistungsempfänger; Theorie; USA